The Story of R.A Kartini As A Source of Ideas For Creating Digital Designs In The Wayang Beber Style (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
The creation of this digital design was inspired by the story of the struggle of R.A. Kartini, a female figure who pioneered women's emancipation in Indonesia. Through a visual approach that combines the style of wayang beber with modern digital design techniques, this work presents a harmony between tradition and innovation. Wayang beber, as one of Indonesia's traditional performing arts, is known for its rich symbolism and narrative power. These values ​​are the main source of inspiration in designing a work that is not only aesthetic, but also full of meaning.By utilizing digital illustration techniques and image manipulation, this design presents distinctive patterns, strong color palettes, and dynamic visual compositions. This visual style not only strengthens the artistic aspect, but also represents the social and cultural values ​​fought for by Kartini—such as equality, education, and freedom of thought for women.